Effects of Thiazolidinone Derivatives Against Buprenorphine-Induced Painful Hypersensitivity in Mice (Molecular Medicine Communications, 2022)
Opioids have been used to treat acute and chronic pain for millennia. It is studied that prolonged use of opioids may result in neuroinflammation and increased pain sensation associated with allodynia, hyperalgesia and increased interleukin-1β (IL-1 β) expression in spinal cord. The present study was designed to investigate the effects of thiazolidinone derivatives against buprenorphine-induced increased pain sensitivity and IL-1 β expression in mice. The albino mice were injected subcutaneously buprenorphine twice daily for two weeks. Thiazolidinone derivatives were injected 30 minutes before buprenorphine injection. Thermal hyperalgesia, mechanical allodynia and tail flick tests performed on day 0, 1, 4, 8, 12 and 16. Mice were sacrificed immediately after behavioral testing and ELISA was performed to measure IL-1β expression in spinal cord. We found that thiazolidinone derivatives reduced latency time during hot plate and tail flick test and increased paw withdrawal threshold as compared to control. Moreover, thiazolidinone derivatives reduced IL-1β expression in spinal cord. Thiazolidinone derivatives might be useful for the management of increased pain sensitivity and neuroinflammation associated with buprenorphine administration.
Keywords: Buprenorphine, Neuroinflammation, Interleukin-1β, Thiazolidinone derivatives, Mice.